Accuracy of a no-biopsy approach for the diagnosis of coeliac disease across different adult cohorts. Issue 5 (2nd November 2020) - Penny, Hugo A; Raju, Suneil A; Lau, Michelle S; Marks, Lauren JS; Baggus, Elisabeth MR; Bai, Julio C; Bassotti, Gabrio; Bontkes, Hetty J; Carroccio, Antonio; Danciu, Mihai; Derakhshan, Mohammad H; Ensari, Arzu; et al.
Abstract : Objective: We aimed to determine the predictive capacity and diagnostic yield of a 10-fold increase in serum IgA antitissue transglutaminase (tTG) antibody levels for detecting small intestinal injury diagnostic of coeliac disease (CD) in adult patients. Design: The study comprised three adult cohorts. Cohort 1: 740 patients assessed in the specialist CD clinic at a UK centre; cohort 2: 532 patients with low suspicion for CD referred for upper GI endoscopy at a UK centre; cohort 3: 145 patients with raised tTG titres from multiple international sites. Marsh 3 histology was used as a reference standard against which we determined the performance characteristics of an IgA tTG titre of ≥10×ULN for a diagnosis of CD. Results: Cohort 1: the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for IgA tTG levels of ≥10×ULN at identifying individuals with Marsh 3 lesions were 54.0%, 90.0%, 98.7% and 12.5%, respectively. Cohort 2: the sensitivity, specificity, PPV and NPV for IgA tTG levels of ≥10×ULN at identifying individuals with Marsh 3 lesions were 50.0%, 100.0%, 100.0% and 98.3%, respectively. Cohort 3: the sensitivity, specificity, PPV and NPV for IgA tTG levels of ≥10×ULN at identifying individuals with Marsh 3 lesions were 30.0%, 83.0%, 95.2% and 9.5%, respectively. Conclusion: Our results show that IgA tTG titres of ≥10×ULN have a strong predictive value at identifying adults with intestinal changes diagnostic of CD. This study supports the use of a no-biopsy approach for the diagnosis of adult CD.